Investigation of progressive failures of corrugated roofing assemblies subjected to static loading using a finite element model - Opiña, Gabriel M.; Acosta, Timothy John S. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Last October 19, 2016, Typhoon Lawin, internationally known as Haima, made landfall on Cagayan province. Typhoon Lawin had a maximum wind speed of 315 kph. According to reports of National Disaster Risk Reduction and Management Council (NDRRMC), 13,966 houses were damaged and 48,521 families were affected by this typhoon making it currently the second most destructive typhoon recorded in the Philippines next to Typhoon Haiyan. Majority of the houses were damaged because of the failure of their roofing assemblies. The failure of the connections in the roofing assemblies often lead to a progressive failure of the entire building envelope. In the Philippines, the common roofing assemblies that are used comprise of corrugated roof sheathings and wood nails and Tek screws as fasteners. There are two types of failures that are observed in a roofing assembly, a pull-out failure, which is the withdrawal of the fasteners from the support, and a pull-through failure, which happens when the roof sheathing has pulled-through the head of the fastener. Unfortunately, there is no design provision yet that is based on minimizing the aforementioned failures. In line with this, a finite element model was developed and analyzed to investigate the progressive failure of the roofing connections by subjecting the model to static wind pressure. The initial failure pressure recorded in the experimental and simulation were 2470 Pa and 2130 Pa respectively. The model was considered validated since the simulation results showed similar behavior to the experimental results. The thickness of the roof sheathing and spacing of fasteners were varied in the validated model. The models were analyzed and results showed that using a thicker roof sheathing improved the pressure capacity from 60% to 100%. On the other hand, using a smaller spacing of fasteners improved the pressure capacity from 34% to 82%
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Roofing; Failure mode and effects analysis